Tying the knot of language: unveiling the linguistic and conceptual tapestry of wedding idioms in English and Spanish - Martín-Gascón, Beatriz (Onomázein, 2024)
This paper delves into the integration of phraseology and cognitive linguistics, using a comparative corpus-based analysis of idiomatic locutions concerning weddings and marriage in English and Spanish. Within a cognitive phraseology framework, the research focuses on their formal and semantic fixation and complexity, and examines their metaphorical motivation. By doing so, it addresses a significant gap in literature, facilitating deeper insights into linguistic and cultural representations of love and wedding traditions. Ultimately, this study advocates for further exploration of marriage idiomatic locutions from a cognitive phraseology perspective offering avenues for broader investigations into cultural traditions associated with love and other emotions.